Muslims and Hindus Encounter on Tolerance at Glanggang Village, Pakisaji, Malang, Indonesia - Riris Masruroh; M. Syaeful Anam (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2023)
The topic of tolerance is still a major topic of discussion in Indonesia. This happens because of the strengthening of identity politics, which results in social division. This research aims to examine and analyze the tolerance of Islam and Hinduism. This paper also looks at the phenomenon of tolerance using Giddens’ concept of structuration. This research method used a qualitative approach by using in-depth interviews, observations, and literature studies to explore information related to this research topic. The findings of this research show the institutionalized social structure of the Glanggang community’s local wisdom values, which social structure shapes the tolerant behavior of the community. Javanese cultural values and the spirit of tolerance in the religious values guide the community to coexist. The collective experience is recorded in social activities and religious activities. The structure allows agents to develop an inclusive spirit of life. Formal and informal agents play an important role in shaping tolerant mindsets and behaviors. It shows the dialectical and mutually influencing relationship between structures and agents. Structures contribute to shaping agents’ actions, but at the same time, agents also reproduce structures.